A Buprenorphine Education and Training Program for Primary Care Residents: Implementation and Evaluation. Issue 3 (July 2013) - Kunins, Hillary V.; Sohler, Nancy L.; Giovanniello, Angela; Thompson, Devin; Cunningham, Chinazo O.
Background: Although substance use disorders are highly prevalent, resident preparation to care for patients with these disorders is frequently insufficient. With increasing rates of opioid abuse and dependence, and the availability of medication-assisted treatment, one strategy to improve resident skills is to incorporate buprenorphine treatment into training settings. Methods: In this study, esidency faculty delivered the BupEd education and training program to 71 primary care residents. BupEd included (1) a didactic session on buprenorphine, (2) an interactive motivational interviewing session, (3) monthly case conferences, and (4) supervised clinical experience providing buprenorphine treatment. To evaluate BupEd, the authors assessed (1) residents' provision of buprenorphine treatment during residency, (2) residents' provision of buprenorphine treatment after residency, and (3) treatment retention among patients treated by resident versus attending physicians. Results: Of 71 residents, most served as a covering or primary provider to at least 1 buprenorphine-treated patient (84.5 and 66.2%, respectively). Of 40 graduates, 27.5% obtained a buprenorphine waiver and 17.5% prescribed buprenorphine. Treatment retention was similar between patients cared for by resident PCPs versus attending PCPs (90-day retention: 63.6% [ n = 35] vs. 67.9% [ n = 152]; P = .55). Conclusion: These results show that BupEd is feasible, provides residents with supervised clinical experience in treating opioid-dependent patients, and can serve as a model to prepare primary care physicians to care for patients with opioid dependence.